2009
DOI: 10.5851/kosfa.2009.29.5.566
|View full text |Cite
|
Sign up to set email alerts
|

Entrapment of Milk Nutrients during Cholesterol Removal from Milk by Crosslinked β-Cyclodextrin

Abstract: This study was designed to elucidate the quantities of milk nutrients entrapped during cholesterol removal from milk by crosslinked β-cyclodextrin (β-CD, 0.4~1.2%, w/v) and to evaluate the amounts of the residual β-CD in cholesterol-reduced milk treated by crosslinked β-CD. The content of lactose in the control milk (without treatment by crosslinked β-CD) was 4.86%, and the amounts of lactose entrapped by crosslinked β-CD ranged from 0.00 to 0.03%. The total amounts of the entrapped short-chain free fatty acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…These results correlated with the study by Kim et al [24]. Furthermore, Ha et al [25] suggested that the free fatty acids in food may be reduced because they are trapped in β-CD cavities molecule. …”
Section: Total Lipidsupporting
confidence: 82%
“…These results correlated with the study by Kim et al [24]. Furthermore, Ha et al [25] suggested that the free fatty acids in food may be reduced because they are trapped in β-CD cavities molecule. …”
Section: Total Lipidsupporting
confidence: 82%
“…The SNF was reduced with increasing the amounts of β -CD, and it was proved that some constituents of milk may entrapped in the cavity of β -CD and leave the environment after separation of β -CD. Ha et al [ 31 ] confirmed the decreasing of some nutritional materials during cholesterol removal processing of cream using β -CD.…”
Section: Resultsmentioning
confidence: 98%
“…Aggregation of fat molecules in raw milk inhibits the inclusion of cholesterol in β -CD molecules. Ha et al [ 25 , 31 ] suggested that the free fatty acids in food may be reduced because they are trapped in β -CD molecule cavities. Kwak et al [ 32 ] reported that cheddar cheese fat content made by milk treated by β -CD was lower than control milk samples.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of all of the results obtained from the present study (on the entrapment of nutrients during cholesterol removal from cream by crosslinked β‐CD), it was suggested that the amounts of nutrients, such as lactose, short‐chain FFA, FAA and water‐soluble vitamins, entrapped during cholesterol removal from cream by crosslinked β‐CD were minimal. In our previous study, it was found that the small amounts of lactose, short‐chain FFA, FAA and water‐soluble vitamins were entrapped during cholesterol removal from milk by crosslinked β‐CD (Ha et al. 2009).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study investigating the quantities of milk nutrients [lactose, short‐chain free fatty acid (FFA), free amino acid (FAA) and water‐soluble vitamin] entrapped during cholesterol removal from milk by crosslinked β‐CD, it was revealed that amounts of entrapped nutrients were negligible during cholesterol removal from milk by crosslinked β‐CD (Ha et al. 2009).…”
Section: Introductionmentioning
confidence: 99%